«ПУТІНІЗМ» ЯК РІЗНОВИД ДЕРЖАВНО-ПОЛІТИЧНОГО РЕЖИМУ ТА СУСПІЛЬНИЙ ФЕНОМЕН - Синяк, Ярослав Васильович; Кріцак, Іван Васильович (SUPREMANCE OF LAW, 2016)
The article deals with the phenomenon of Putinism as a kind of public-political regime that determines the Russian Federation annexation towards Ukraine and other sovereign states. That was found out that Putinism as a regime pronounce chauvinism, which promotes revanchist mood among the population of Russia and promotes the war. The author concludes that Putinism was formed with the connivance and the general indifference of the Russian people to the regime. At the same time Russian people cannot be considered as an enemy to Ukrainian or other nations of the civilized world.
Keywords: Putinism; the kind of public-political regime; chauvinism; hybrid warfare; the security